1997
DOI: 10.1046/j.1525-1497.1997.012004230.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Aging and Hormone Replacement Therapy Hormonal Levels, Symptoms, and Attitudes of African-American and White Women

Abstract: OBJECTIVES:To characterize reproductive hormone levels, symptoms, and attitudes related to menopause among healthy, menstruating white and African-American women aged 44 to 49 years. DESIGN: Pilot study; cross-sectional survey. SETTING:Community-based convenience sample of women in the Philadelphia metropolitan area. PARTICIPANTS:Thirty-three African-American and 35 white women. MEASUREMENTS:The survey instrument collected demographic data, medical and reproductive history, health practices and behaviors. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Study findings that include women in all phases of menopause are conflicting. 8,9,13,[41][42][43] Two large surveys of multiethnic, perimenopausal and postmenopausal women found similar differences in menopausal symptoms by race. A cross-sectional survey of nearly 15,000 multiethnic women, ages 40-55 years, found that African American women were significantly more likely to report vasomotor symptoms than white women and that women in the perimenopausal and postmenopausal periods were more likely to note vasomotor symptoms than those who were premenopausal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Study findings that include women in all phases of menopause are conflicting. 8,9,13,[41][42][43] Two large surveys of multiethnic, perimenopausal and postmenopausal women found similar differences in menopausal symptoms by race. A cross-sectional survey of nearly 15,000 multiethnic women, ages 40-55 years, found that African American women were significantly more likely to report vasomotor symptoms than white women and that women in the perimenopausal and postmenopausal periods were more likely to note vasomotor symptoms than those who were premenopausal.…”
Section: Discussionmentioning
confidence: 92%
“…White women were also more than twice as likely to note that their provider inquired about their symptoms compared with African American women (51.4% vs. 21.2%). 43 Our study had a relatively small sample size and included postmenopausal women of moderately high socioeconomic status who volunteered to participate in a randomized clinical trial to evaluate the effect of soy intake on lipid levels as well as menopausal symptoms. Thus, generalizability is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, culture is associated with attitudes toward menopausal symptoms and perceptions of impairment. Blacks generally espouse more positive attitudes toward menopause than whites (Standing & Glazer, 1992; Pham et al . 1997), and do not see their symptoms as impairing or disruptive to their functioning (Im et al .…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 For example, a study of white and African American women reported that African American women had a more positive perception of menopausal changes where cessation of menses brought relief from worrying about the burden of pregnancy. 4,8 Conversely, white women perceived menopause to be a medical problem for which they should seek medical treatment. 4 Clearly, multiple psychosocial, physical, and cultural factors can be powerful determinants of how women perceive and experience the menopausal transition.…”
mentioning
confidence: 99%